2016
DOI: 10.1016/j.eats.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

All-Endoscopic Single-Row Repair of Full-Thickness Gluteus Medius Tears

Abstract: Abductor tendon tears typically develop insidiously in middle-aged women and can lead to debilitating lateral hip pain and a Trendelenburg limp. The gluteus medius tendon is most commonly torn and may show fatty degeneration over time, similar to the rotator cuff muscles of the shoulder. Endoscopic repair offers a therapeutic alternative to traditional open techniques. This article describes the workup, examination, and endoscopic repair of a full-thickness gluteus medius tear presenting as lateral hip pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…With advances in hip arthroscopic techniques, research has focused on endoscopic repairs of gluteus medius tears. 8,13,30,40,42,52,55 Voos et al 55 reported results on 10 patients with an average follow-up of 25 months after endoscopic gluteus medius repair and noted mHHS and HOS of 94 and 93 points, respectively. Furthermore, the patients' motor strength was 5 of 5.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in hip arthroscopic techniques, research has focused on endoscopic repairs of gluteus medius tears. 8,13,30,40,42,52,55 Voos et al 55 reported results on 10 patients with an average follow-up of 25 months after endoscopic gluteus medius repair and noted mHHS and HOS of 94 and 93 points, respectively. Furthermore, the patients' motor strength was 5 of 5.…”
Section: Discussionmentioning
confidence: 99%
“…at a high-volume academic hospital with a technique that has been described in the literature. 12 A standard anterolateral portal was established under fluoroscopic guidance and an anterior portal was established under direct visualization. The modified midanterior portal was established via spinal needle localization under direct arthroscopic visualization.…”
Section: Operative Techniquementioning
confidence: 99%
“…While a number of conditions are associated with GTPS including trochanteric bursitis, external coxa saltans and gluteal tendinopathy ( 3 , 4 , 8 ), better understanding of the condition along with advanced imaging and surgical findings has revealed a common cause to be hip abductor tendon (HAT) tears ( 2 , 9 , 10 ). While Bunker et al ( 11 ) first reported on the high incidence of HAT tears in patients with femoral neck fractures, numerous open and endoscopic techniques have been presented since this time ( 12 - 35 ), with the majority of these over the past 5 years. Recent reviews highlighted a higher number of reported surgical complications with open repair techniques, though no differences in strength or clinical scores ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%